Trákija és Elláda - határ nélküli világ. Újabb kihívások és lehetőségek - Uzunova, Liana (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The lecture is trying to carry on and expand with practices from new region of Strandja the issues of the Bulgarian-Greek cooperation in the region of the Rhodopes, presented on the II. Regions in Carpathian Basin conference, which took place in Kaposvár on 22-th of May 2009.